Perceived social contribution and its associations with political participation - Ellen C. Reinhart; Monique M. Turner; David M. Markowitz; Dustin Carnahan (PLoS ONE, 2025)
Many people who are eligible to participate in the political process do not, suggesting the interests of a large portion of the electorate are not adequately represented in government. While some past work has found that subjective well-being is related to political engagement, less is known about which specific aspects of well-being might drive this effect. We propose and test the idea that self-perceived social contribution – the belief that one’s life and everyday activities provide something of value to society – is related to multiple forms of political participation, likely because people who believe they provide something of value to society feel more integrated with society and therefore may be more likely to act on its behalf via political participation. Two correlational studies (N = 3,729) with data from distinct points in American politics (1996 and 2024) find that individuals with greater self-perceived social contribution were more likely to intend to vote, be willing to engage in activism, seek rather than avoid election information (Study 1), and donate to and volunteer for political causes (Study 2). Further, Study 2 provides empirical support for the previously theorized components of social contribution, providing evidence that self-efficacy and social responsibility underlie this construct in political contexts. Together, these studies identify a specific dimension of well-being that is related to multiple forms of political participation and suggests that fostering feelings of social contribution may promote democratic engagement.